Heat-induced whey protein microparticulation under continuous shear in acidic conditions. (December 2021) - Homer, Stephen; Lundin, Leif; Dunstan, Dave E.
Abstract: Investigations were undertaken into the effect of shear rate, temperature profile, pH and protein concentration on aggregate formation upon heating of whey protein solutions at pH 2.0 and 3.5. Shear rate, protein concentration and pH had notable effects, while the temperature profile was found to have a minimal effect on the final aggregate size. At higher concentrations, aggregate sizes decreased as shear increased, while at lower concentrations, the opposite was observed. Additionally, pH impacted the extent of change in aggregate size at the two concentrations investigated. Based on previous findings in the literature and the results obtained herein, it is proposed that particle size is governed, not just by concentration, but the effective concentration and that it is the primary driver in determining the aggregate size produced from whey protein solutions exposed to simultaneous heating and shearing. A mechanism has been proposed to explain the effects of pH, concentration and shear rate on whey protein aggregate size. Graphical abstract: Image 1 Highlights: Effective concentration is key to determining the size of heat-induced aggregates. Mechanism for the effect of shear on aggregate size is proposed. Critical gelation concentration linked to effective concentration. Aggregation at low pH shows similarities to published works at higher pH values. Different heating profiles had only a minor impact on particle size.